Key Account Planning: Benefits, Barriers and Best Practice. - Ryals, Lynette; Rogers, B (Taylor & Francis, 2007)
Although strategic planning has been part of the management function for as long as anyone can remember, the emergence of key account plans as a critical subset of the marketing plan in business-to-business markets has not attracted much analysis. This gap needs to be addressed, as key account plans have their own unique complexities. Moreover, the importance of key account plans is increasing. There is a need for a more widespread understanding of the benefits of key account planning, encompassing processes and outputs. Based on a four- phase research project in 78 international companies, this paper describes current best practice in key account planning and plans. The research demonstrates the benefits of key account planning and sets out a framework for implementing key account planning as a business process. The paper goes on to describe the contents of a key account plan and to note some common defects found in such plans.
Keywords: Marketing planning; key account planning; key account management